Challenges and Perspectives of Neurological Disorders - Kung, Woon-Man; Ningrum, Dina Nur Anggraini (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint offers a comprehensive and updated overview of the current state-of-the-art techniques in the management of various neurological disorders. These disorders include neurodegenerative diseases, neurovascular disorders, and neuro-oncological diseases. The reprint also presents the latest advances and innovations in the diagnosis, treatment, and prevention of these complex conditions, emphasizing the role of cutting-edge technologies, such as neurobiology, neuroimaging, neuroinformatics, neuropharmacology, and neurosurgery. This reprint is a useful resource for researchers, clinicians, students, and anyone interested in the current challenges and perspectives of neurological disorders.